A Rare Anomaly of Biliary System: MRCP Evidence of a Cystic Duct Cyst - Cemil Goya; Mehmet Serif Arslan; Alpaslan Yavuz; Cihad Hamidi; Suzan Kuday; Mehmet Hanifi Okur; Bahattin Aydogdu (Case Reports in Radiology)
Cystic duct cysts are a rare congenital anomaly. While the other bile duct cysts (choledochus and the intrahepatic bile ducts) are classified according to the classification described by Tadoni, there is no classification method described by the cystic duct cysts, although it is claimed that the cystic duct cysts may constitute a new “Type 6” category. Only a limited number of patients with cystic duct cysts have been reported in the literature. The diagnosis is usually made in the neonatal period or during childhood. The clinical symptoms are nonspecific and usually include pain in the right upper quadrant and jaundice. The condition may also present with biliary colic, cholangitis, cholelithiasis, or pancreatitis. In our case, the abdominal ultrasonography (US) performed on a 6-year-old female patient who presented with pain in the right upper quadrant pointed out an anechoic cyst at the neck of the gall bladder. Based on the magnetic resonance cholangiopancreatography (MRCP) results, a cystic dilatation was diagnosed in the cystic duct. The aim of this case-report presentation was to discuss the US and MRCP findings of the cystic dilatation of cystic duct, which is an extremely rare condition, in the light of the literature information.